Evaluating a gamified bystander program: Evidence from two randomized online field experiments - Axel Ebers; Stephan L. Thomsen (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2022)
Objective: Previous social-psychological research has demonstrated the positive effects of online bystander programs on various crime-related outcomes, while information systems research has demonstrated the ability of gamification to improve motivation, engagement, and learning. This study bridges the gap between social psychology and information systems research by evaluating a bystander program that combines the simulation of a dangerous situation in a virtual environment with the application of game principles and game design elements. Method: We developed three research hypotheses and tested them using two randomized online field experiments (RCTs). During the first experiment, we collected data from 4,188 users on Facebook and randomly assigned them to four treatment arms, including three different configurations of the treatment and one control group. During the second experiment, we collected data from a representative sample of the population and observed them across three waves. Results: The results from the first experiment support the hypotheses that the bystander program motivates people to intervene in violent situations and that gamification enhances the motivational effect. The results from the second experiment support the hypothesis that the program makes people feel more capable of intervening. They also show that the treatment effects persist over a long period of time and hold for the overall population. Conclusions: We conclude that the gamification approach offers great potential for bystander education and that social media are well suited for the dissemination and upscaling of bystander programs. Policymakers can use these findings to improve the effectiveness and efficiency of future bystander programs or similar prevention measures.
Keywords: C93; D91; K42; 330; Bystander Intervention; Gamification; Program Evaluation; Field Experiments; Social Media